"Calidad de la carne de cordero pelibue (ovis aries) bajo distintos métodos y periodos de conservación, en el Cantón El Empalme año 2014". - Cañarte Hidalgo, Kevin Ivan (2014)
This research was conducted in the village of El Empalme Guayas Province. With geographic coordinates: Latitude 1° 02'46 ", longitude 79 ° 38'01" and altitude 71 msnm. In assessing meat on macro and micro nutrients they did in the lab UTE Extension Santo Domingo de los Tsáchilas. Design was used in this investigation Completely Random factorial arrangement (A x B) time (0, 20, 40 and 60 days) conservation with 6 replicates per treatment (8 treatments) with, giving a total of 48 experimental units to remove the differences in average, the multiple range test of Tukey at 5% probability was used. 40 kg of mutton were used. Each sample of lamb contained 200 grams. In the pH in dried salted beef had an average of 6,40 and 6,23, acceptable was 60 days with a mean of 5,89. The moisture of the meat jerky outperformed average of 35,67% and 38,40% moisture in salted meat. Ash had higher average jerky with 23,70% and fat, salted meat protein with 16,01% and 35,70% respectively. In the macronutrients of lamb meat preservation method for drying had a high percentage of phosphorus, potassium and calcium with an average of 0,57; 0,35 and 0,34%, respectively, had a high percentage of phosphorus, potassium, calcium and magnesium averaging 0,40; 0,30; 0,49 and 0,10%, but a high percentage of phosphorus, potassium and calcium per day 0 with averages of 0,45 was taken; 0,35 and 0,67%, but a higher percentage of magnesium after 60 days of storage with 0,13% .In micronutrients lamb meat preservation method for drying introduce high performance copper, iron, zinc and manganese with averages of 6,28; 54,79; 56,16 and 2,99 ppm respectively All samples meet the INEN RULES and economic analysis the dried pork posted a net profit of $ 15,40 per pound of meat.